Mechanistic insights into the activities of major families of enzymes in bacterial peptidoglycan assembly and breakdown - Kwan, Jeric Mun Chung (2023)
Serving as an exoskeletal scaffold, peptidoglycan is a polymeric macromolecule that is essential and conserved across all bacteria, yet is absent in mammalian cells; this has made bacterial peptidoglycan a well-established excellent antibiotic target. In addition, soluble peptidoglycan fragments derived from bacteria are increasingly recognised as key signalling molecules in mediating diverse intra- and inter-species communication in nature, including in gut microbiota-host crosstalk. Each bacterial species encodes multiple redundant enzymes for key enzymatic activities involved in peptidoglycan assembly and breakdown. In this review, we discuss recent findings on the biochemical activities of major peptidoglycan enzymes, including peptidoglycan glycosyltransferases (PGT) and transpeptidases (TPs) in the final stage of peptidoglycan assembly, as well as peptidoglycan glycosidases, lytic transglycosylase (LTs), amidases, endopeptidases (EPs) and carboxypeptidases (CPs) in peptidoglycan turnover and metabolism. Biochemical characterisation of these enzymes provides valuable insights into their substrate specificity, regulation mechanisms and potential modes of inhibition.